Unraveling the nexus of NAD+ metabolism and diabetic kidney disease: insights from murine models and human data - Yang, Sisi; Gong, Weiyuan; Wang, Yujia; Hao, Chuanming; Guan, Yi (Frontiers in Endocrinology, 2024)
Background: Nicotinamide adenine dinucleotide (NAD+) is a critical coenzyme involved in kidney disease, yet its regulation in diabetic kidney disease (DKD) remains inadequately understood. Objective: Therefore, we investigated the changes of NAD+ levels in DKD and the underlying mechanism. Methods：Alternations of NAD+ levels and its biosynthesis enzymes were detected in kidneys from streptozotocin-induced diabetic mouse model by real-time PCR and immunoblot. The distribution of NAD+ de novo synthetic enzymes was explored via immunohistochemical study. NAD+ de novo synthetic metabolite was measured by LC-MS. Human data from NephroSeq were analyzed to verify our findings. Results: The study showed that NAD+ levels were decreased in diabetic kidneys. Both mRNA and protein levels of kynurenine 3-monooxygenase（KMO）in NAD+ de novo synthesis pathway were decreased, while NAD+ synthetic enzymes in salvage pathway and NAD+ consuming enzymes remained unchanged. Further analysis of human data suggested KMO, primarily expressed in the proximal tubules shown by our immunohistochemical staining, was consistently downregulated in human diabetic kidneys. Conclusion:Our study demonstrated KMO of NAD+ de novo synthesis pathway was decreased in diabetic kidney and might be responsible for NAD+ reduction in diabetic kidneys, offering valuable insights into complex regulatory mechanisms of NAD+ in DKD.